2014
DOI: 10.3390/ijms151019134
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of 430 Chinese Cynodon dactylon Accessions Using Sequence-Related Amplified Polymorphism Markers

Abstract: Although Cynodon dactylon (C. dactylon) is widely distributed in China, information on its genetic diversity within the germplasm pool is limited. The objective of this study was to reveal the genetic variation and relationships of 430 C. dactylon accessions collected from 22 Chinese provinces using sequence-related amplified polymorphism (SRAP) markers. Fifteen primer pairs were used to amplify specific C. dactylon genomic sequences. A total of 481 SRAP fragments were generated, with fragment sizes ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…This showed that these SRAP markers are highly useful and can effectively be used in the genetic diversity studies. Out of these 340 fragments, 328 (96.58%) were recognized as polymorphic fragments which is higher than 91% reported by Wang et al [24] and lower than 100% detected by Gulsen et al [12] and Huang et al [25]. The high level of polymorphism indicates that the high level of genetic diversity exists in the germplasm of bermudagrass.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This showed that these SRAP markers are highly useful and can effectively be used in the genetic diversity studies. Out of these 340 fragments, 328 (96.58%) were recognized as polymorphic fragments which is higher than 91% reported by Wang et al [24] and lower than 100% detected by Gulsen et al [12] and Huang et al [25]. The high level of polymorphism indicates that the high level of genetic diversity exists in the germplasm of bermudagrass.…”
Section: Discussionmentioning
confidence: 69%
“…Molecular markers have significant advantages over morphological and isozyme markers because they are uninfluenced by growth and environmental conditions and can be applied from any growth phase. A wide variety of molecular marker types have been applied to evaluate the genetic diversity of bermudagrass, including DNA amplification fingerprinting (DAF) [ 8 10 ], randomly amplified polymorphic DNA (RAPD) [ 11 , 12 ], amplified fragment length polymorphism (AFLP) [ 13 17 ], inter-simple sequence repeat (ISSR) [ 12 , 18 21 ], simple sequence repeat (SSR) [ 21 23 ], peroxidase gene polymorphism (POGP) [ 12 ] and sequence-related amplified polymorphism (SRAP) [ 12 , 24 , 25 ] markers.…”
Section: Introductionmentioning
confidence: 99%
“…The later one demonstrated that C. arcuatus separated from another seven species, and the species had different chromosome numbers clustered in all instances, indicating a close relationship between 2x and 4x [27]. Since then, more and more molecular markers have been used in genetic diversity analysis of Cynodon accessions, such as AFLP, ISSR, RAPD, SRAP and SSR (details in Table 3) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Khanal et al [44] successfully applied sugarcane EST-SSR analysing genetic diversity among triploid hybrids, tetraploid C. dactylon and diploid C. transvaalensis.…”
Section: Evaluation and Use Of Genetic Resourcesmentioning
confidence: 99%
“…The protocol is simple, efficient, and has a high production rate. It has been used successfully in genetic diversity analysis and construction of genetic maps of many plant species [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%